2016
DOI: 10.3233/jpd-160804
|View full text |Cite
|
Sign up to set email alerts
|

Ventilatory Dysfunction in Parkinson’s Disease

Abstract: In contrast to some other neurodegenerative diseases, little is known about ventilatory dysfunction in Parkinson’s disease (PD). To assess the spectrum of ventilation disorders in PD, we searched for and reviewed studies of dyspnea, lung volumes, respiratory muscle function, sleep breathing disorders and the response to hypoxemia in PD. Among the studies, we identified some limitations: (i) small study populations (mainly composed of patients with advanced PD), (ii) the absence of long-term follow-up and (iii)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 65 publications
1
52
0
2
Order By: Relevance
“…However, in the open thorax, only H was increased in PD. The data collected suggest, for the first time, that stiffening in the ribcage could have an effect on the distension and relaxation that occurs during a normal breath in PD animals (Baille et al., ; Hampson et al., ). Additionally, we verified abnormal collagen fibre deposition in alveolar septa and in airways in PD‐induced animals.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, in the open thorax, only H was increased in PD. The data collected suggest, for the first time, that stiffening in the ribcage could have an effect on the distension and relaxation that occurs during a normal breath in PD animals (Baille et al., ; Hampson et al., ). Additionally, we verified abnormal collagen fibre deposition in alveolar septa and in airways in PD‐induced animals.…”
Section: Discussionmentioning
confidence: 98%
“…Breathing problems are recognized as a cause of morbidity and mortality in patients with Parkinson's disease (PD), caused by neural damage in specific regions of the ventral medulla that are responsible for rhythm generation and chemoreception, such as the preBötzinger complex (preBötC) and retrotrapezoid nucleus (RTN), respectively (Baille et al., ; Benarroch, Schmeichel, Low, & Parisi, ; Owolabi, Nagoda, & Babashani, ; Seccombe et al., ; Torsney & Forsyth, ). Previous studies have also found that PD patients showed a reduction of pulmonary volumes and stiffening of respiratory muscles, indicating an impairment directly in the lung, ribcage and/or the muscles responsible for breathing (Baille et al., ; LeWitt et al., ; Owolabi et al., ; Seccombe et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…As yet there have not been any systematic studies of the natural history of dyspnea and ventilatory dysfunction during the course of the disease or whether they undergo fluctuations, as in the case of other non‐motor symptoms . Only a few studies have specifically investigated the effect of levodopa on respiratory symptoms, and have found a poor correlation with changes in measures of lung function …”
Section: Dyspnea In Pd and Underlying Mechanismsmentioning
confidence: 99%
“…18 Only a few studies have specifically investigated the effect of levodopa on respiratory symptoms, and have found a poor correlation with changes in measures of lung function. 4,19 In addition to being a contributory factor to dyspnea during daytime activities, diaphragmatic dysfunction is of particular importance in relation to nocturnal hypoventilation and sleep-disordered breathing (SDB). Moreover, functional disturbances of brainstem control centers, which are crucial to maintaining involuntary rhythmogenic ventilatory drive during sleep, could lead to impaired nocturnal ventilation and respiratory sleep disorders.…”
Section: Dyspnea In Pd and Underlying Mechanismsmentioning
confidence: 99%
“…The association between PD and respiratory dysfunction is poorly understood; however, some studies have shown that structures in the medulla oblongata, known to control respiratory depth and rate, may be affected by the initial neurodegeneration of the disease (De De Keyser & Vincken, 1985;Kazemi & Johnson, 2002;Braak et al, 2003). In this way, lung function changes may occur, with abnormal levels of lung volume and ventilatory function, as well as changes in inspiratory and expiratory muscle strength, and may appear in the early stages of the disease (Baille et al, 2016;Baille et al, 2018;Pal, Sathyaprabha, Tuhina, & Thennarasu, 2007;Polatli, Akyol, Çildağ, & Bayülkem, 2001;Wang et al, 2014). And, according to Baille et al (2016), individuals with PD may present restrictive, obstructive, or mixed disturbance.…”
mentioning
confidence: 99%